Toxidromes for Working Dogs - McMichael, Maureen A.; Singletary, Melissa; Akingbemi, Benson T. (Frontiers in Veterinary Science, 2022)
Terrorist attacks with biological and chemical warfare agents are increasing in frequency worldwide. Additionally, hazardous chemical accidents, illicit drug laboratories and intentional poisonings are potential sites for exposure to working dogs. Working dogs play a crucial role in law enforcement, military and search and rescue teams. Their intelligence, agility and strength make them ideal partners to be deployed to these natural disaster sites, terrorist attacks and industrial accidents. This, unfortunately, leads to increasing exposure to chemical and biological weapons and other hazardous substances. First responders have little to no training in emergency care of working dogs and veterinarians have very little training on recognition of the clinical signs of many of these agents. In order to ensure a rapid medical response at the scene first responders and veterinarians need a primer on these agents. Identifying a specific agent amidst the chaos of a mass casualty event is challenging. Toxidromes are a constellation of clinical and/or laboratory findings that allow for rapid identification of the clinical signs associated with a class of toxin and have been helpful in human medical triage. Focusing on a class of agents rather than on each individual toxin, allows for more expedient administration of antidotes and appropriate supportive care. This article reviews toxidromes for the most common chemical weapons with a special emphasis on clinical signs that are specific (and different) for canines as well as appropriate antidotes for working canines. To our knowledge, there are no publications describing toxidromes for working dogs.